2019
DOI: 10.1002/ece3.4990
|View full text |Cite
|
Sign up to set email alerts
|

Release from natural enemies mitigates inbreeding depression in native and invasive Silene latifolia populations

Abstract: Inbreeding and enemy infestation are common in plants and can synergistically reduce their performance. This inbreeding ×environment (I × E) interaction may be of particular importance for the success of plant invasions if introduced populations experience a release from attack by natural enemies relative to their native conspecifics. Here, we investigate whether inbreeding affects plant infestation damage, whether inbreeding depression in growth and reproduction is mitigated by enemy release, and whether this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…The assumption that sex-specific viability selection plays a role in the expression of inbreeding depression seems likely for S. latifolia. Previous research elaborated that females of this species experience resource depletion stress more often than males in the late growing season during fruit maturation (Gehring and Monson, 1994) and that inbreeding reduces resistance to environmental stress (Schrieber et al, 2018(Schrieber et al, , 2019. Another non-exclusive explanation for the different inbreeding effects on female versus male S. latifolia may be found in sexual selection.…”
Section: The Cost Of Inbreeding For Floral Traits Is Higher In Females Than Malesmentioning
confidence: 99%
“…The assumption that sex-specific viability selection plays a role in the expression of inbreeding depression seems likely for S. latifolia. Previous research elaborated that females of this species experience resource depletion stress more often than males in the late growing season during fruit maturation (Gehring and Monson, 1994) and that inbreeding reduces resistance to environmental stress (Schrieber et al, 2018(Schrieber et al, , 2019. Another non-exclusive explanation for the different inbreeding effects on female versus male S. latifolia may be found in sexual selection.…”
Section: The Cost Of Inbreeding For Floral Traits Is Higher In Females Than Malesmentioning
confidence: 99%
“…The field sampling, rearing conditions and experimental crossing are described in detail in (Schrieber et al, 2018(Schrieber et al, , 2019. Seeds were dried and stored at room temperature until use.…”
Section: Plant Materialsmentioning
confidence: 99%
“…As colonization events are associated with successive demographic bottlenecks, purging is expected to be one determinant for the successful establishment and proliferation of plant populations in novel habitats (Facon et al, 2011;Schrieber and Lachmuth, 2017). However, only few empirical studies verified the role of purging in plant colonization success by revealing significantly lower inbreeding depression following experimental crossings in invasive than native plant populations (Rosche et al, 2016;Schrieber et al, 2019). Again, the focus of these studies was on fitness components rather than floral attractiveness traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Campbell et al 2013;Kariyat et al 2012;Kristensen et al 2010). Recent empirical studies support that inbreeding x environment interactions can prevent or foster successful invasion (Hufbauer et al 2013;Rosche et al 2017;Schrieber et al 2019), while molecular studies suggest that epigenetic modifications play a decisive role in stress responses (Chinnusamy and Zhu 2009) and the expression of inbreeding depression. For example, a study on Scabiosa columbaria (a self-compatible but predominantly outcrossing species) revealed that inbreeding caused inbreeding depression for fitness-related traits and increased methylation levels (Vergeer et al 2012).…”
Section: The Potential Role Of Epigenetics In the Expression Of Inbrementioning
confidence: 99%